2014
DOI: 10.1530/joe-13-0488
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish pituitary gene expression before and after sexual maturation

Abstract: Sexual maturation and somatic growth cessation are associated with adolescent development, which is precisely controlled by interconnected neuroendocrine regulatory pathways in the endogenous endocrine system. The pituitary gland is one of the key regulators of the endocrine system. By analyzing the RNA sequencing (RNA-seq) transcriptome before and after sexual maturation, in this study, we characterized the global gene expression patterns in zebrafish pituitaries at 45 and 90 days post-fertilization (dpf). A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
1
16
0
2
Order By: Relevance
“…Pituitary α-MSH affects background adaption in teleost3, and zebrafish melanosomes disperse rapidly in response to α-MSH63. However, the lack of melanocortin receptor expression in the pituitary64 (and Supplementary Fig. S3) would suggest that such hypophysiotropic activity, if exists, is mediated by a different type of receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Pituitary α-MSH affects background adaption in teleost3, and zebrafish melanosomes disperse rapidly in response to α-MSH63. However, the lack of melanocortin receptor expression in the pituitary64 (and Supplementary Fig. S3) would suggest that such hypophysiotropic activity, if exists, is mediated by a different type of receptor.…”
Section: Discussionmentioning
confidence: 99%
“…In our laboratory, we observed a 25% increase in the body weight of PGC-null dnd morphants at 5 months of age compared with male sibling wildtype control zebrafish (unpublished data, Figure 1). This demonstrates the balance between the networks regulating somatic growth and reproduction Analysis of the global gene expression patterns in the zebrafish pituitary during the juvenile and sex maturation stages revealed that luteinizing hormone β (lhb) is the only pituitary hormone transcript to exhibit a significant change in expression between 45 and 90 dpf [48]. A decrease in spermatic parameters and reproductive success has been observed in GH overexpressing zebrafish males [124].…”
Section: Interaction Between the Endocrine Regulations On Somatic Gromentioning
confidence: 98%
“…Similarly, their specific receptors, ghrh-rs, are abundant in the hypothalamus, telencephalon, spinal cord, diencephalon, and pituitary, but only present at low levels in the ovary [44,47]. Based on our recent pituitary transcriptome studies, the levels of both ghrh and ghrh-r expression were less than 1 RPKM in the zebrafish pituitary at both 45 and 90 d post-fertilization (dpf) [48]. Both ghrh and ghrh-r are expressed in the head region of zebrafish during the embryonic stage.…”
Section: Growth Hormone-releasing Hormone (Ghrh)mentioning
confidence: 99%
“…The constructions of the cDNA library and cDNA sequencing and comparison were performed by BGI. The expression analyses were performed as described previously (16).…”
Section: Methodsmentioning
confidence: 99%